Comparison of the therapeutic effect of amniotic fluid stem cells and their exosomes on monoiodoacetate‐induced animal model of osteoarthritis. (18th October 2019) - Zavatti, Manuela; Beretti, Francesca; Casciaro, Francesca; Bertucci, Emma; Maraldi, Tullia
Abstract: The cartilage tissue engineering associated with stem cell‐related therapies is becoming very interesting since adult articular cartilage has limited intrinsic capacity for regeneration upon injury. Amniotic fluid stem cells (AFSC) have been shown to produce exosomes with growth factors and immunomodulating molecules that could stop tissue degradation and induce cartilage repair. Based on this state of the art, the main aim of this study was to explore the efficacy of the secreted exosomes, compared to their AFSC source, in MIA‐induced animal model of osteoarthritis mimicking a chronic and degenerative process, where inflammation is also involved and lead to irreversible joint damage. Exosomes, obtained by the use of a commercial kit, prior to the injection in animal knee joints, were characterized for the presence of typical markers and HGF, TGFβ, and IDO. Then, analyses were performed by histology, immunohistochemistry, and behavioral scoring up to 3 weeks after the treatment. Exosome‐treated defects showed enhanced pain tolerance level and improved histological scores than the AFSC‐treated defects. Indeed by 3 weeks, TGFβ‐rich exosome samples induced an almost complete restoration of cartilage with good surface regularity and with the characteristic of hyaline cartilage. Moreover, cells positive for resolving macrophage marker were more easily detectable into exosome‐treated joints. Therefore, a modulating role for exosomes on macrophage polarization is conceivable, as demonstrated also by experiments performed on THP1 macrophages. In conclusion, this study demonstrates for the first time the efficacy of human AFSC exosomes in counteract cartilage damage, showing a positive correlation with their TGFβ content.